2010
DOI: 10.1115/1.4001386
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy Effects on Thermal Boundary Layer Over a Vertical Plate With a Convective Surface Boundary Condition

Abstract: This study aims to analyze the effects of thermal buoyancy on the laminar boundary layer about a vertical plate in a uniform stream of fluid under a convective surface boundary condition. Using a similarity variable, the governing nonlinear partial differential equations have been transformed into a set of coupled nonlinear ordinary differential equations, which are solved numerically by applying shooting iteration technique together with fourth-order Runge-Kutta integration scheme. The variations in dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 8 publications
6
112
0
Order By: Relevance
“…Makinde et al (2010) reported a local similarity solution for the effect of buoyancy forces on thermal boundary layer over a flat plate with a convective boundary condition. Their result also revealed that the buoyancy effects tend to reduce the thermal boundary layer thickness.…”
Section: Abstract: Steady Laminar Natural Convection Of Mhd Flow Overmentioning
confidence: 99%
See 1 more Smart Citation
“…Makinde et al (2010) reported a local similarity solution for the effect of buoyancy forces on thermal boundary layer over a flat plate with a convective boundary condition. Their result also revealed that the buoyancy effects tend to reduce the thermal boundary layer thickness.…”
Section: Abstract: Steady Laminar Natural Convection Of Mhd Flow Overmentioning
confidence: 99%
“…Soret and Dufour effects on hydro magnetic Heat and Mass Transfer over a Vertical Plate with a Convective Surface Boundary Condition and Chemical reaction were studied by Gangadhar (2013). Makinde et al (2010) reported a local similarity solution for the effect of buoyancy forces on thermal boundary layer over a flat plate with a convective boundary condition. Their result also revealed that the buoyancy effects tend to reduce the thermal boundary layer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The physical quantities of interest are the skin friction coefficient (C f x ) and the local Nusselt number (N u x ), which are defined as 19) where the surface shear stress τ w and the surface heat flux q w are given by τ w = µ f ∂u ∂y and q w = −k nf ∂T ∂y + (q r )w at y = 0, (2.20)…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Recently, Ishak [15] reported the steady laminar boundary layer flow over a permeable flat plate with convective boundary conditions. The effect of thermal buoyancy along a stationary vertical plate with a uniform free stream flow were studied by Makinde and Olanrewaju [19]. Bég et al [1] studied the mixed magneto-convective flow of an electrically conducting flow along a moving radiating vertical flat plate with hydrodynamic slip and thermal convective boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A numerical method has been applied to the problem of heat and mass transfer over a flat plate embedded in a porous medium in the presence of magnetic field such as (Bachok et al (2010), Makinde and Aziz (2010), Makinde andAziz (2011), Makinde (2010), and Merkin(1979)). Makinde and Olanrewaju (2010) extended the work of Aziz (2009) to the presence of buoyancy force. Fathizadeh and Rashidi (2009) study convective heat transfer equations of boundary layer in presence of pressure gradient over a flat plate.…”
Section: Introductionmentioning
confidence: 99%